2021
DOI: 10.3390/ijms22147720
|View full text |Cite
|
Sign up to set email alerts
|

Induced Cardiomyocyte Proliferation: A Promising Approach to Cure Heart Failure

Abstract: Unlike some lower vertebrates which can completely regenerate their heart, the human heart is a terminally differentiated organ. Cardiomyocytes lost during cardiac injury and heart failure cannot be replaced due to their limited proliferative capacity. Therefore, cardiac injury generally leads to progressive failure. Here, we summarize the latest progress in research on methods to induce cardiomyocyte cell cycle entry and heart repair through the alteration of cardiomyocyte plasticity, which is emerging as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…Many studies have explored novel therapeutics to promote cardiac regeneration to replenish cardiomyocyte numbers. 21,52,53 One study tested the novel concept that recapitulating the embryonic hypoxic environment, where low oxygen levels in the fetus supports the embryo development and cardiac growth, could reawaken adult myocyte proliferative properties. 23 In that study adult male mice were subjected to hypoxia (7% oxygen) and the results suggested an induction of large amounts of cardiomyocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have explored novel therapeutics to promote cardiac regeneration to replenish cardiomyocyte numbers. 21,52,53 One study tested the novel concept that recapitulating the embryonic hypoxic environment, where low oxygen levels in the fetus supports the embryo development and cardiac growth, could reawaken adult myocyte proliferative properties. 23 In that study adult male mice were subjected to hypoxia (7% oxygen) and the results suggested an induction of large amounts of cardiomyocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously showed that cardiomyocyte cell cycle induction after MI leads to a significant functional improvement in the heart (Abouleisa et al, 2022;Mohamed et al, 2018;Salama et al, 2022;Salama et al, 2021;Shapiro et al, 2014). In addition, our previous studies showed that 4F is an effective tool for inducing cell cycle and complete cytokinesis, which results in improved cardiac function after MI (Abouleisa et al, 2022;Mohamed et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…To identify the target protein for the NDPPC that mediates cardiomyocyte proliferation, Autodock tool and Autodock vina software were used. First, we screened the 2D and 3D structures of NDPPC against the most prominent human cell cycle gene activators and inhibitors (Salama et al, 2021). The screening revealed that NDPPC has a binding affinity to p38⍺ MAP kinase similar to SB203580, a known inhibitor of p38α MAPK (Birkenkamp et al, 2000) (Figure 2).…”
Section: In Silico Target Prediction Revealed That Ndppc Is a Potent ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, complexes of cyclins/CDKs in adult mammalian CMs are constitutively inhibited by the CIP/KIP family (p21, p27, and p57) and the INK4 family (p16, p15, p18, and p19). Since the decline in the proliferative capacity of post-mitotic CMs might be due to the downregulation of cyclins/CDKs and upregulation of CIP/KIP family and INK4 family, whether the intervention with these cell-cycle regulators might induce CM cell-cycle entry has been widely investigated ( Salama et al, 2021 ). For example, overexpression of cyclin A2 in murine and porcine infarcted hearts improved heart function, and activated the cell cycle in CMs ( Woo et al, 2006 ; Cheng et al, 2007 ; Shapiro et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%